2021
DOI: 10.3126/jota.v4i1.40680
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Cultural Diversity Impact in Hospitality Industry Leadership: Managerial Communication Perspective from Five Star Hotels in Kathmandu Valley, Nepal

Abstract: This study aims to measure the cultural diversity impacts in hospitality industry leadership from the perspective of managerial communication. Data were obtained from all the 10 five star hotels in Kathmandu valley. 167 respondents were sampled from the managers of five star hotels in Kathmandu valley, Nepal using structured questionnaire. Data analysis is made using descriptive analysis and Leadership Practices Index measured through dimension suggested by GLOBE Model. The study found out that maximum majorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Kathmandu Valley is taken as area of this study as Newars are the historical inhabitants of Kathmandu Valley and was already famous for its architecture and apparently enlightened governance (Goodman, 2016). Kathmandu Valley is divided into three districts: Kathmandu, Lalitpur, and Bhaktapur, which collectively cover an area of 899 square kilometers, with a total area of 665 square kilometers (Paudel et al, 2021). The Kathmandu Valley is located between the latitudes of 27o 32' 13" and 27o 49' 10" north, and the longitudes of 85o 11' 31" and 85o 31' 38" east, with a mean elevation of 1,300 meters (4,265 feet) above sea level (Jimee, 2006).…”
Section: Study Area and Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Kathmandu Valley is taken as area of this study as Newars are the historical inhabitants of Kathmandu Valley and was already famous for its architecture and apparently enlightened governance (Goodman, 2016). Kathmandu Valley is divided into three districts: Kathmandu, Lalitpur, and Bhaktapur, which collectively cover an area of 899 square kilometers, with a total area of 665 square kilometers (Paudel et al, 2021). The Kathmandu Valley is located between the latitudes of 27o 32' 13" and 27o 49' 10" north, and the longitudes of 85o 11' 31" and 85o 31' 38" east, with a mean elevation of 1,300 meters (4,265 feet) above sea level (Jimee, 2006).…”
Section: Study Area and Populationmentioning
confidence: 99%
“…Results shows that 97% respondents revealed that such issue can be solved whereas 3% of respondents revealed that such issue cannot be tackled by the Newari community regarding cultural tourism development. Respondents also opined that such challenges in cultural tourism development faced by Newari community can be tackled with different strategies such as economic benefits generated from flow of tourism (43), creation of sustainable relationship (60), conservation with adequate cultural resources (98), and integrating cultural, tourism and national/local development strategies (71). In order to promote Cultural Tourism Development, respondents suggest that participation of youth, intervention of government, society and municipalities, awareness programs, promotion, participation and packages, tourist potential and conservation, protection and development of cultural management are the betterment strategies of cultural tourism development (see figure 28).…”
Section: Managerial Solution Regarding Cultural Tourism Developmentmentioning
confidence: 99%
“…Cultural diff erences within and across countries can result in confl ictive communication; therefore, communication strategies such as confl ict resolution may provide an important means of bridging diverse cultural perspectives, (Tingtoomey et al, 2000;Devkota et al, 2021a;Paudel et al, 2021) equality does not always appear in the expected places. Additionally even in the present rush toward global expansion, the literature has given only limited attention to the role of culture in service marketing (Winsted, 1997;Mattila, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Multicultural issues in the workplace are more pervasive, complex, and subtle, however, than simply questions about what language or languages will be spoken. Even when people of diff erent racial and cultural backgrounds speak the same language, they have diffi cultly communicated with one another (Paudel et al, 2021). People from diff erent cultural back-grounds bring diff erent meanings, values, assumptions, and discourse styles into the workplace conversation; such diff erences oft en lead to misunderstandings and breakdowns in communication, and can threaten a common orientation to organizational goals (Fine, 2018;Devkota et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation